2012
DOI: 10.1021/bi301043k
|View full text |Cite
|
Sign up to set email alerts
|

Differential Furanose Selection in the Active Sites of Archaeal DNA Polymerases Probed by Fixed-Conformation Nucleotide Analogues

Abstract: DNA polymerases select for the incorporation of deoxyribonucleotide triphosphates (dNTPs) using amino acid side-chains that act as a “steric-gate” to bar improper incorporation of rNTPs. An additional factor in the selection of nucleotide substrates resides in the preferred geometry for the furanose moiety of the incoming nucleotide triphosphate. We have probed the role of sugar geometry during nucleotide selection by model DNA polymerases from Sulfolobus solfataricus using fixed conformation nucleotide analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…An siRNA duplex containing a ribo-N-MC modification in the guide strand was taken up by the intracellular RNAi machinery and showed near-wildtype activity and target mRNA degradation (Terrazas et al 2011). A crystal structure of a N-MC-dATP nucleotide bound at the active site of the model DNA polymerase Dpo4 superimposed nearly perfectly with an unmodified dATP bound at the same site, demonstrating selectivity of the polymerase for the North substrate conformation (Ketkar et al 2012a), and no protein contacts to the cyclopropane ring were observed in either Dpo4 or human DNA polymerase iota (Ketkar et al 2012b). Both N-MC and S-MC nucleotides have been shown to reproduce the preferences of the corresponding unmodified nucleotides for rotamers at the sugar-base glycosidic bond (torsion angle χ) and ring-adjacent C3 ′ -C4 ′ bond (γ) (Marquez et al 1997(Marquez et al , 2004.…”
mentioning
confidence: 99%
“…An siRNA duplex containing a ribo-N-MC modification in the guide strand was taken up by the intracellular RNAi machinery and showed near-wildtype activity and target mRNA degradation (Terrazas et al 2011). A crystal structure of a N-MC-dATP nucleotide bound at the active site of the model DNA polymerase Dpo4 superimposed nearly perfectly with an unmodified dATP bound at the same site, demonstrating selectivity of the polymerase for the North substrate conformation (Ketkar et al 2012a), and no protein contacts to the cyclopropane ring were observed in either Dpo4 or human DNA polymerase iota (Ketkar et al 2012b). Both N-MC and S-MC nucleotides have been shown to reproduce the preferences of the corresponding unmodified nucleotides for rotamers at the sugar-base glycosidic bond (torsion angle χ) and ring-adjacent C3 ′ -C4 ′ bond (γ) (Marquez et al 1997(Marquez et al , 2004.…”
mentioning
confidence: 99%
“…The distinct behaviors of the DNA pols vis-à-vis nucleotides of opposite puckers were also seen with the B-family Dpo1 and Y-family Dpo4 pols from the archaeal hyperthermophile Sulfolobus solfataricus . Thus, the former inserts both the N- and S-MC-dATPs with relatively minor reductions in efficiency, whereas the latter only inserts N-MC-dATP ( 208 ). Dpo4 was then unable to extend; extensions by Dpo1 from the MC-dA nucleotides were inhibited in both cases relative to dA, whereby incorporation following S-MC-dA was slightly favored.…”
Section: Second-generation Modificationsmentioning
confidence: 99%
“…Phylogenetic analysis of the polymerases categorizes them into six branches: two branches containing prokaryotic UmuC homologs (found in gram-positive and gram-negative bacteria); the DinB-like enzymes with homologs in all three domains of life (bacteria, archaea and eukaryotes); and three branches consisting of eukaryotic Rad30A (pol η), Rad30B (pol ι) and Rev1 proteins (Ohmori et al , 2001). The structure and biochemical properties of prokaryotic (bacterial DinB paralogs and pol V), archaeal (Dbh and Dpo4), and eukaryotic (pols η, ι, κ, and Rev1) polymerases have been investigated in great detail by several groups with some of these studies focusing on the characterization of sugar recognition by these enzymes (Brown et al , 2010b; DeLucia et al , 2003; DeLucia et al , 2006; Donigan et al , 2014; Jarosz et al , 2006; Katafuchi et al , 2010; Ketkar et al , 2012; Kirouac et al , 2011; Kuban et al , 2012; McDonald et al , 2012; Niimi et al , 2009; Ordonez and Shuman, 2014; Ordonez et al , 2014; Sherrer et al , 2010; Shimizu et al , 2003; Vaisman et al , 2012a). Akin to their widely divergent capacities to promote lesion bypass, the ability of the Y-family polymerases to discriminate between rNTPs and dNTPs varies considerably.…”
Section: Sugar Selectivity Of Tls Polymerases From Different Phylogenmentioning
confidence: 99%